Discussion on Halal Assurance for Micro and Small Business: A Bibliometric and Content Analysis - Anita Priantina; Safeza Mohd Sapian; Devinna Pramitha; Aufa Aufa (University of Darussalam Gontor, 2023)
The integration and comprehensiveness of the halal system are essential for ensuring halal assurance. The issue of halal certification has become a topic of interest, particularly when considering micro and small businesses. Various perspectives have been examined in the study of halal certificates. In Indonesia, the implementation of Halal Assurance Law no 33 Year 2014 has made halal certification mandatory at the national level. This requirement poses challenges, particularly for small and micro businesses that typically have limited resources. This research analyzes current trends and discussions surrounding halal studies in relation to micro and small businesses. The Google Scholar Database is utilized to ensure broader coverage. The research employs bibliometric analysis and systematic literature review to address the research questions. The study reveals that limited resources are frequently cited as a significant problem for micro and small enterprises. To ensure the implementation of halal assurance practices in these businesses, sustainable support is necessary, considering their constrained financial capabilities.